Physiotherapists' experiences with a four-week mindfulness-based stress reduction program. (3rd September 2021) - Pappous, Athanasios (Sakis); Mohammed, Warhel Asim; Sharma, Dinkar
Abstract: Objective: The study sought to gather the perceptions and experiences of a group of physiotherapists who took part in mindfulness-based stress reduction program (MBSR). Methods: Semi-structured interviews were conducted with eight physiotherapists who took part in a four-week formal and self-directed mindfulness meditation program. The data collected were analysed by implementing a thematic analysis. Results: Themes were identified in relation to perceived health benefits (stress reduction and increased attentiveness), the perceived impact of the MBSR on their professional practice and the perceived difficulties in practicing mindfulness. Conclusion: The data from this study offer qualitative evidence that mindfulness practise can become an important element in a physiotherapists' stress reduction toolkit, by helping them deal with the challenges of their professional practise. The main difficulties encountered with the program were related to the feelings of sleepiness that MBSR induced in them in the beginning. The participants also reported that the long duration of the sessions was another obstacle, suggesting that a brief form of meditation would be preferable and more convenient.